Desarrollo de un plan de fortalecimiento para el área de pasantías del programa Administración de Negocios (2015)
“La Universidad del Quindío” was founded on October 14, 1960 is a public institution under the Ministry of National Education, has 33 undergraduate degree programs and 18 graduate, which provides training for people of integrity. Among its academic programs Business Administration initiating an agreement with the Universidad Industrial de Santander in 2000, the May 30, 2006 he received the qualifying record by resolution of the Ministry of National Education No 2565 for classroom methodology, code is SNIES 52168. From the approval by the ministry enrollment and tuition for the period 2006-2, for which 40 students were enrolled 65 enrolled opened. Moreover is the area of internships which began operations in 2012 with five students and five agreements with local companies, this process has been strengthened through the years, now it has 85 agreements and more than 100 trainees in process. Thus the idea of a building plan for the area of internships which will increase visibility for documentation, process improvement and strategies to achieve business arises.